2023
DOI: 10.1002/marc.202300420
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Engineering of Fillable Gradient Structure into Flexible Capacitive Pressure Sensor Toward Ultra‐High Sensitivity and Wide Working Range

Weiqiang Hong,
Xiaohui Guo,
Tianxu Zhang
et al.

Abstract: Tactile sensing is required for electronic skin and intelligent robots to function properly. However, the dielectric layer's poor structural compressibility in conventional pressure sensors results in a limited pressure sensing range and low sensitivity. To solve this issue, a flexible pressure sensor with a crocodile‐inspired fillable gradient structure is provided. The fillable gradient structure and grooves in the pressure sensor accommodate the deformed microstructure that permits the enhancement of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Researchers and developers are already actively investigating tactile sensors due to their ease of access to acquisition data and applicability to applications. Tactile sensors are mainly classified into four sensing mechanisms: capacitive [16][17][18][19][20], piezoresistive [21][22][23][24], piezoelectric [25][26][27], and triboelectric [28][29][30], among which capacitive tactile sensors with a simplified structure, easy signal acquisition, and low-power consumption have become a research hotspot for researchers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and developers are already actively investigating tactile sensors due to their ease of access to acquisition data and applicability to applications. Tactile sensors are mainly classified into four sensing mechanisms: capacitive [16][17][18][19][20], piezoresistive [21][22][23][24], piezoelectric [25][26][27], and triboelectric [28][29][30], among which capacitive tactile sensors with a simplified structure, easy signal acquisition, and low-power consumption have become a research hotspot for researchers [31].…”
Section: Introductionmentioning
confidence: 99%
“…With the need for booming developments in the fields of flexible wearable devices, smart healthcare, human–computer interaction, electronic skin, and smart electro-textiles (e-textiles), , persistent studies on flexible electronic devices , have become more urgent and indispensable. Flexible electronic devices are flexible, thin low-cost, and have adjustable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Through the above research, it has been found that the range of the sensor has been greatly improved, but the sensor cannot better adapt to different scene requirements in different pressure ranges. So, wide range flexible pressure sensors are still a research difficulty and there is a great demand in practical applications. Meanwhile, most existing pressure sensors are designed for specific application scenarios, and their sensing range and corresponding sensitivity are often immutable, making them unable to flexibly adapt to different load applications. Therefore, designing a capacitive pressure sensor with a simple structure, wide detection range, better performance trade-off and flexibility is of great value to better meet different needs in practical applications and avoid replacing sensors with different ranges.…”
Section: Introductionmentioning
confidence: 99%